PENDEKATAN PER SE ILLEGAL DAN RULE OF REASON DALAM HUKUM PERSAINGAN (PERBANDINGAN INDONESIA-MALAYSIA) - Hanif Nur Widhiyanti (Arena Hukum, 2015)
AbstractApproach to the nature of illegal per se and rule of reason prohibition has long been applied in determining whether an act hinder competition or not. Competition law of Indonesia and Malaysia also implement a ban properties per se illegal or rule of reason, but did not mention explicitly in the formulation of laws and regulations. The unfirm arrangement model imposes a difficult responsibility for institution of business competition authorities to be able to precisely define the reference as a measure that should be used in assessing an anti-competitive act. This research is a normative law with legislation approach and comparative law. From the discussion, it was concluded that the application of the nature of illegal per se and rule of reason prohibition in Law No. 5 of 1999 and the Competition Act 2010 of Malaysia implemented through an assessment of how the result level of an anti-competitive actions capable of distorting the market and blocking, thus eliminating competition completely. Consideration was also made based on the alignment between normative rules in the Act with the basic theory of competition itself. Thus, the rule of law in the enforcement of competition law can be maintained.Key words: competition, per se illegal, rule of reasonsAbstrakBaik pendekatan sifat larangan per se illegal maupun rule of reason telah lama diterapkan dalam menetapkan apakah suatu perbuatan menghambat persaingan ataukah tidak. Hukum Persaingan Indonesia dan Malaysia pun menerapkan sifat larangan per se illegal atau rule of reason namun tidak menyebutkan secara tegas dalam rumusan peraturan perundang-undangannya. Model pengaturan tidak secara tegas tersebut, telah membebankan sebuah tanggung jawab yang tidak mudah bagi lembaga otoritas persaingan usaha untuk mampu secara tepat mulai dari menentukan acuan sebagai ukuran yang harus digunakan dalam menilai sebuah perbuatan anti persaingan. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan dan pendekatan perbandingan hukum. dari hasil pembahasan disimpulkan, penerapan sifat larangan per se illegal ataukah rule of reason dalam Undang-Undang Nomor 5 Tahun 1999 dan Akta Persaingan 2010 Malaysia ialah selain melalui sebuah penilaian bagaimana tingkatan akibat dari sebuah perbuatan anti persaingan mampu mendistorsi pasar dan menghalangi hingga menghilangkan persaingan sama sekali. Pertimbangan juga di dasarkan kepada keselarasan antara peraturan normatif dalam Undang-Undang dengan teori dasar persaingan itu sendiri. Dengan demikian kepastian hukum dalam penegakan hukum persaingan dapat terus ditegakkanKata kunci: persaingan, per se illegal dan rule of reason